Analisis Efektivitas Penghapusan Barang Milik Daerah (BMD) dalam Mengoptimalkan Manajemen Aset pada BPKAD Kabupaten Dompu - Irfan Irfan; Mahmud Mahmud; Fahrul Mauzu (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study evaluated the effectiveness of regional property disposal at the Regional Financial and Asset Management Agency of Dompu Regency, which faced significant challenges regarding human resource capacity and inventory inaccuracy. The researchers applied a qualitative descriptive approach and collected data through direct observations, in-depth interviews, and documentation studies. The results indicated that the disposal procedure was executed effectively in accordance with standard regulations through rigorous physical verification. Furthermore, the constraint of limited staff quantity was successfully mitigated by digitalizing the inventory system, while the issue of untraceable physical assets was resolved strictly through financial compensation claims. The study concluded that the effective disposal of severely damaged assets successfully prevented the waste of the regional budget and facilitated the systematic planning of future asset requirements.